Performance measures, benchmarking and the best practices in the new economy - Gunasekaran, A.; Putnik, Goran, 1954- (Emerald, 2006)
Organisations employ performance measures and benchmarking to promote and implement best practices in order to improve competitiveness. Considering the importance of performance measures and benchmarking in organizational competitiveness, this e-book attempts to cover the topics of performance measures, benchmarking and best practices in new economy in all types of business organizations. The objective is to facilitate advances in the theory and practice of performance measures and benchmarking and in turn to implement and promote companies' best practices in the new economy, at all organisati.